Exploring Management Practices in the Hospitality Industry: A Comprehensive Employee Perspective (International Journal of Atharva, 2024)
This study explores management practices within the hospitality industry from the perspective of employees, focusing on various aspects of management effectiveness and employee engagement. A questionnaire survey was conducted among employees from different hospitality establishments, revealing a significant gender disparity in representation, with 75.4% male and 26.6% female respondents. Key findings indicate a strong consensus among participants regarding the importance of quality management practices, with a majority supporting new management styles aimed at enhancing quality across departments. Senior executives were generally perceived as effective communicators of company policies, with 53% of respondents expressing agreement on this matter. Furthermore, a notable percentage (76.1%) of employees acknowledged the responsibility of top management in ensuring quality performance. Leadership capability among managers was deemed essential, with 51.5% of participants strongly agreeing on its significance. Continuous self-improvement among managers received substantial support (44.8% agreement), alongside recognition of the necessity for information sharing among departmental managers. The results also highlighted a prevailing focus on quality strategies within hotels, with 47.8% of respondents agreeing that their establishments prioritize quality over quantity.